O comportamento do setor de telefonia móvel brasileiro após a privatização das telecomunicações - Porfírio, Mirella Magalhães (2012)
The privatization of the telecommunications sector in Brazil, caused structural changes in the market, going from state monopoly to a nearby structure of competitive markets. To prove this notion of evolution, were calculated for the mobile industry, some indices of industrial concentration, namely: market share, concentration ratios (CR), Herfindahl-Hirschman Index (HH) and Theil entropy index (ET) by the number of cell phones by operators (inThousands) in the period 2000 to 2010, with all these measures confirming the decentralization of the mobile market in the last decade.